A rare case of isolated cysticercus involvement of inferior rectus muscle presenting with upward gaze restriction. (October 2016) - Khanduri, Sachin; Agrawal, Sumit; Singh, Anshita; Bhadury, Samarjit
Cysticercosis is a parasitic infection caused by larvae known as cysticercus cellulosae. Orbital cysticercosis is usually a part of generalised systemic infestation. Isolated infection of the extra-occular muscle is an extremely rare entity. Involvement of orbital adnexas are rare even if associated with brain infection. Here, we report a case of an 18-year-old boy who presented with eccentric proptosis and restriction in upward gaze and was diagnosed with cysticercosis of inferior rectus.